The benefit of elobixibat in chronic constipation is associated with faecal deoxycholic acid but not effects of altered microbiota. Issue 5 (20th July 2020) - Misawa, Noboru; Higurashi, Takuma; Takatsu, Tomohiro; Iwaki, Michihiro; Kobayashi, Takashi; Yoshihara, Tsutomu; Ashikari, Keiichi; Kessoku, Takaomi; Fuyuki, Akiko; Matsuura, Tetsuya; Ohkubo, Hidenori; Usuda, Haruki; et al.
Summary: Background: Elobixibat, a novel inhibitor of apical sodium‐dependent bile acid transporter for treating chronic constipation, increases colonic bile acid concentrations, stimulating bowel function. However, it is not clear which bile acids are altered, or whether altered gut microbiota are associated with functional effects that may alter bowel function. Aims: To investigate the effects of elobixibat on changes in the faecal concentrations of total and individual bile acids and in faecal microbiota. Methods: This was a prospective, single‐centre study. After baseline period, patients received 10 mg daily of elobixibat for 2 weeks. We evaluated the effects on bowel function, changes in faecal bile acid concentrations and composition of gut bacteria, before and after elobixibat administration. Results: In the 30 patients analysed, the frequency of pre‐ and post‐treatment bowel movements per fortnight was 7 and 10 ( P  < 0.001), respectively. The pre‐treatment faecal bile acid concentration increased significantly from 10.9 to 15.0 µg/g stool post‐treatment ( P  = 0.030), with a significant increase in faecal deoxycholic acid (pre‐treatment 3.94 µg/g stool to post‐treatment 5.02 µg/g stool, P  = 0.036) and in glycine‐conjugated deoxycholic and chenodeoxycholic acids. Shannon index was significantly decreased, but there were no significant changes at the genus and phylum levels. Conclusions: Short term treatment with elobixibat increased the concentrations of total bile acids and deoxycholic acid and decreased the diversity of faecal microbiota. The biological effects of elobixibat are associated with its effects on secretory bile acids, rather than the structural changes of an altered faecal microbiota.